Welcoming the Creator Economy for Content Creators: Trends, Challenges, and Insights - William Ben Gunawan; Putri Anggraini Setyaningsih (Universitas Syiah Kuala, 2026)
The creator economy is transforming digital entrepreneurship, with individuals monetizing content through online platforms. Projected to grow significantly in the following decade, this sector thrives on AI-driven personalization, blockchain monetization, and demand for authentic content. However, financial instability, algorithmic dependence, and income unpredictability persist, with the majority of creators relying primarily on brand deals. This study conducts a bibliometric analysis of Scopus-indexed publications using VOSviewer to visualize publication metrics, geographical networks, and keyword co-occurrences, followed by a literature review. Findings reveal key research themes and challenges, including monetization volatility, regulatory concerns, and platform dependency. To foster a sustainable creator economy, diversification of revenue streams, platform transparency, and supportive policies are essential. Insights from this study can guide content creators in strategic decisions, assist platforms in improving creator support, and inform stakeholders and policymakers in shaping fairer digital labor regulations, ensuring long-term financial stability and innovation.